2021
DOI: 10.1038/s41398-021-01687-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of symptoms in first episode psychosis: a longitudinal network approach

Abstract: Early psychosis is characterised by heterogeneity in illness trajectories, where outcomes remain poor for many. Understanding psychosis symptoms and their relation to illness outcomes, from a novel network perspective, may help to delineate psychopathology within early psychosis and identify pivotal targets for intervention. Using network modelling in first episode psychosis (FEP), this study aimed to identify: (a) key central and bridge symptoms most influential in symptom networks, and (b) examine the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 64 publications
2
11
1
Order By: Relevance
“…It is somewhat surprising that our findings are contrary to other network analyses, which have observed that nodes that belong to the same subscale are highly interconnected [ 5 , 42 , 43 ]. However, it should be noted that a direct comparison of our findings with those of previous studies is not feasible in most of the cases due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It is somewhat surprising that our findings are contrary to other network analyses, which have observed that nodes that belong to the same subscale are highly interconnected [ 5 , 42 , 43 ]. However, it should be noted that a direct comparison of our findings with those of previous studies is not feasible in most of the cases due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
“…In keeping with the present results, a recent longitudinal study in an FEP sample found that depression was one of the most important nodes in their network [43] and further revealed that it maintained its central role at the 12-month follow-up despite the amelioration of psychotic symptoms [46]. The topographic proximity of depressive to positive symptoms in our network is also consistent with previous findings [5,43,48] and constitutes an alert that potential worsening of the affective domain could translate to a flare up of psychotic symptoms [43] and vice versa. However, their networks did not include general psychopathology, so the present study raises the possibility that other nodes may underlie these relationships.…”
Section: Bridges Nodessupporting
confidence: 91%
See 2 more Smart Citations
“…Based on previous research, we hypothesized that feelings of sadness and feelings of worthlessness would be identified as central symptoms in the network [ 27 , 31 ] and potentially as bridges between depression and psychosis symptoms and risk factors. We also hypothesized that hallucinations and thoughts of conspiracy against oneself would similarly be identified as central symptoms [ 29 , 30 ] and potentially as bridges in the symptom network. We expected that both genetic risk [ 34 , 35 ] and the lifetime experience of traumatic events [ 36 , 37 ] would be associated with functional impairment, and that among the area-level risk factors evaluated, neighborhood deprivation [ 15 , 18 ] would have the strongest links with depression and psychosis symptoms.…”
Section: Introductionmentioning
confidence: 99%